Binding of a Vitis riparia dehydrin to DNA. (October 2019) - Boddington, Kelly F.; Graether, Steffen P.
Highlights: Dehydrins protect DNA from reactive oxygen species. Binding occurs mainly through the lysine-rich conserved segments. The interactions do not depend on the DNA sequence nor on the presence of metals. Abstract: Plants must protect themselves from abiotic stresses such as drought, cold, and high salinity. The common thread of all three stresses is that they cause dehydration, which in turn promotes the formation of reactive oxygen species (ROS). Dehydrin proteins (dehydrins) are a large family of proteins that have been identified in nearly all land plants, and whose presence is correlated with plant protection from abiotic stresses. Several dehydrin studies have shown that some dehydrins localize to the nucleus, as well as the cytoplasm, but a functional role for nuclear dehydrins has not yet been determined. We show here that the Vitis riparia dehydrin VrDHN1 localizes to the nucleus and is able to bind to DNA to protect it from damage caused by hydrogen peroxide, an ROS source. We also show that the binding to DNA is not DNA-sequence specific, suggesting that the protein is able to protect any exposed DNA without interfering with its normal function. NMR studies show that the binding is largely driven by the lysine-rich nature of dehydrins located in the conserved K-segments. Unlike other, previously studied dehydrins, VrDHN1 binding to DNA is not enhanced through the presence of metals. Lastly, we demonstrate that the Y-segment does not bind ATP, as has long been proposed.